Exploring multitasking proteins in Xanthomonas secretomes: Insights into mechanisms of plant-pathogen interactions - Assis, Renata de Almeida Barbosa; Ferreira, Rafael Marini [UNESP]; de Oliveira, Amanda Carolina Paulino [UNESP]; Carvalho, Flávia Maria Souza [UNESP]; Ferro, Jesus Aparecido [UNESP]; de Souza, Robson Francisco; Orellano, Elena Graciela; Almeida, Nalvo Franco; Garcia, Camila Carrião Machado; Dandekar, Abhaya M.; Chakraborty, Sandeep; Varani, Alessandro M. [UNESP]; et al. (Elsevier, 2025)
Recent advances in large-scale functional genomic analysis have significantly increased interest in multitask proteins. The role of these proteins in Xanthomonas phytopathogens, a model for plant-pathogen interaction studies, remains largely underexplored. In this study, we introduce an innovative systematic comparative analysis of secretomes from 18 different Xanthomonas species, integrating data from multiple proteomic studies to identify potential multitasking proteins. This approach led to the identification of 93 proteins primarily involved in central metabolism that are secreted under various physiological conditions, including 16 previously characterized moonlighting proteins. Promiscuity analysis of five selected enzymes revealed that three (asparaginase, chorismate mutase, and phosphoenolpyruvate synthase) exhibit high potential for catalyzing reactions with non-canonical substrates, suggesting additional functional roles beyond their primary enzymatic activities. Additionally, we re-annotated previously hypothetical secreted proteins, assigning functions related to central metabolism and indicating a high potential for promiscuous activity. This comprehensive compilation of potential moonlighting and promiscuous proteins in Xanthomonas provides new insights into the molecular mechanisms driving plant-pathogen interactions and establishes a foundation for future experimental validations of these multifunctional proteins.
Keywords: Adaptation; Comparative secretome; Moonlight proteins; Multitask proteins; Plant-pathogen interactions; Promiscuous proteins